Respuesta :

The simplified form of the expression is [tex]\frac{14+5\sqrt{3}}{11}[/tex]

How to rationalize surd functions?

Given the surd function expressed as:

[tex]\frac{\sqrt{3} +5}{\sqrt{3} - 5 }[/tex]

Multiply by the conjugate of the denominator to have:
[tex]= \frac{\sqrt{3} +5}{\sqrt{3} - 5 } \times \frac{\sqrt{3} +5}{\sqrt{3} + 5 } \\=\frac{\sqrt{9}+5\sqrt{3}+5\sqrt{3}+25 }{3-25}[/tex]

Simplify the resulting expression
[tex]\\=\frac{3+10\sqrt{3}+25 }{-22}\\=\frac{28+10\sqrt{3}}{-22} \\= \frac{14+5\sqrt{3}}{11}[/tex]

Hence the simplified form of the expression is [tex]\frac{14+5\sqrt{3}}{11}[/tex]

Learn more on rationalization here: https://brainly.com/question/14261303